The survival of micromycetes and yeasts under the low-temperature plasma generated in electrical discharge - Soušková, H; Scholtz, V; Julák, J; Kommová, L; Savická, D; Pazlarová, J (Folia microbiologica, 2011)
The fungicidal effect of low-temperature plasma generated by positive direct current discharge and its influence on the growth dynamics was evaluated on three micromycete species and yeast in water suspensions. The fungicidal effect was lower than analogous bactericidal effect and differs substantially among various fungal species. Together with the cidal effects, the slower growth of exposed fungal spores was observed.
Keywords: houby; Spores, Fungal; mikrobiální viabilita; Yeasts; Sterilization; Electricity; Microbial Viability; kvasinky; elektřina; sterilizace; krevní plazma; Fungi; Plasma; spory hub